A Study on Sasak’s Local Wisdom in Supporting Tourism Development in Central Lombok Regency - Z, Yenti; Zed, Mestika; Erianjoni, Erianjoni (Sumatra Journal of Disaster, Geography and Geography Education, 2018)
The purpose of this research was to study local wisdom of traditional people of Sasak Tribe in supporting tourism development in Central Lombok Regency. The method being used was a descriptive qualitative method. The result found that traditional people of Sasak Tribe had their own uniqueness, for example: 1) Custom Home of Sasak Tribe. The Custom Home was made of wood and had bamboo wicker wall and rumbia leaf roof. The floor was constructed from a mixture of soil, chaff ash and tree sap, smeared and polished with buffalo dung. 2) Handycraft. Women of Sasak Tribe are very skilfull in weaving. It had been taught since they were kids. A Sasak woman was not allowed to marry if she was not yet able to weave. Children aged 9 to 10 years were proficient in weaving. 3) Marriage system of Sasak Tribe. In Sasak Tribe culture, the marriage was carried out with the tradition of kidnapping a potential wife by potential husband which was also named after kawin culik (kidnapping marriage).